The Implementation of Merdeka Belajar Policy in East Java - Ahid, Nur; Sufirmansyah, Sufirmansyah (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
This article aims to reveal the planning, implementation, constraints, and solutions of Merdeka Belajar policy in East Java. This article was written based on field research using a qualitative case study approach. Data were collected through interviews, observation, and documentation. Furthermore, the data were analyzed using the Miles-Huberman version of the interactive qualitative data analysis technique. This article concludes that the planning for the implementation of Merdeka Belajar policy in East Java is carried out through two activities. The first activity was the socialization of the four pillars of Merdeka Belajar from the Indonesian Ministry of Education and Culture. The second activity is to prepare infrastructure such as Dapodik and e-learning systems to support the implementation of the Merdeka Belajar policy. Then, Merdeka Belajar in East Java was implemented through three concrete steps. The first is to carry out the instructions of the Ministry of Education and Culture as optimally as possible under the capabilities of each institution. The second is to join the Motivating School program. The third is optimizing the implementation of student-centered online learning. The implementation of Merdeka Belajar in East Java encountered two main obstacles. The first is the uneven understanding and readiness of teachers in applying the concept of Merdeka Belajar. The second is the delay in the implementation of online learning due to the varied economic backgrounds of the parents of students and the uneven readiness of institutions in conducting online learning. Two solutions are carried out to overcome the obstacles faced in the implementation of Merdeka Belajar in East Java. The first is to strengthen teachers' understanding of the concept and implementation of Merdeka Belajar through outreach activities and workshops. The second is conducting limited face-to-face learning while working on the implementation of blended learning.